Confronting the Monolith: Insider Accounts of the Nature and Techniques of Corruption in Nigeria. Issue 2 (June 2022) - Zakari, Musa Bala; Button, Mark
This paper draws upon insider accounts of the nature and techniques of corruption in Nigeria. It draws upon unique access to interview 20 senior officials employed in key public agencies in the fight against corruption in Nigeria and access to 20 case files of prosecutions by the Independent Corrupt Practices and other related offences Commission (ICPC). The paper illustrates their perception of the monolith of corruption faced and shows some of the most common types of corruption confronted such as embezzlement, theft and fraud; procurement fraud; favoritism, nepotism and related acts; extortion and bribery. The paper also illustrates the connection between the private and public sector in corruption and some of the differences that emerge in grand and petty corruption.